Efeito positivo da suplementação dietética com farinha de resíduo de uva para cordeiros lactentes sobre o ganho de peso, perfil metabólico, leucograma, proteinograma e resposta antioxidante. - Molosse, Vitor Luiz (2020)
The objective of this study was to determine whether the addition of grape residue flour (GRF) in the diet of suckling lambs would improve their health and consequently enhance their growth. We used 48 lambs, 30 days of age divided into four treatments with four repetitions each, with each repetition consisting of three animals. The groups were identified as follows: G-0%, used as a control (without GRF) and G-0.5%, G-1% and G 2% referring to treatment with grape residue flour in doses of 0.5%, 1%, and 2% of inclusion in the concentrate, respectively. Lambs in groups G-1% and G-2% had higher final body weights, weight gain and average daily gain (ADG) compared to the other groups. GRF dietary supplementation had good antioxidant potential, being able to stimulate glutathione S-transferase (GST) activity and consequently reduce levels of reactive oxygen species (ROS) in lambs that consumed the highest dose of GRF (G-2%). GRF supplementation improved humoral responses, with increased serum levels of heavy-chain and light-chain immunoglobulins; however, there was a reduction in serum ceruloplasmin levels in these lambs. We observed higher concentrations of glucose and triglycerides in lambs in the 2% group. There were lower lymphocyte counts in lambs that received GRF. Lambs supplemented with the highest doses of GRF (G-1% and G 2%) had lower total bacterial counts in the feces. We conclude that the use of GRF in the supplementation of suckling lambs improved animal health, as it stimulated the antioxidant and immune systems and consequently favored their growth.